Gut microbiome signature and nasal lavage inflammatory markers in young people with asthma - Sampaio Dotto Fiuza B; Machado de Andrade C; Meirelles PM; Santos da Silva J; de Jesus Silva M; Vila Nova Santana C; Pimentel Pinheiro G; Mpairwe H; Cooper P; Brooks C; Pembrey L; Taylor S; et al. (Elsevier Inc on behalf of the American Academy of Allergy, Asthma & Immunology (AAAAI), 2024)
BACKGROUND: Asthma is a complex disease and a severe global public health problem resulting from interactions between genetic background and environmental exposures. It has been suggested that gut microbiota may be related to asthma development; however, such relationships needs further investigation. OBJECTIVE: This study aimed to characterize the gut microbiota as well as the nasal lavage cytokine profile of asthmatic and nonasthmatic individuals. METHODS: Stool and nasal lavage samples were collected from 29 children and adolescents with type 2 asthma and 28 children without asthma in Brazil. Amplicon sequencing of the stool bacterial V4 region of the 16S rRNA gene was performed using Illumina MiSeq. Microbiota analysis was performed by QIIME 2 and PICRUSt2. Type 2 asthma phenotype was characterized by high sputum eosinophil counts and positive skin prick tests for house dust mite, cockroach, and/or cat or dog dander. The nasal immune marker profile was assessed using a customized multiplex panel. RESULTS: Stool microbiota differed significantly between asthmatic and nonasthmatic participants (P = .001). Bacteroides was more abundant in participants with asthma (P < .05), while Prevotella was more abundant in nonasthmatic individuals (P < .05). In people with asthma, the relative abundance of Bacteroides correlated with IL-4 concentration in nasal lavage samples. Inference of microbiota functional capacity identified differential fatty acid biosynthesis in asthmatic compared to nonasthmatic subjects. CONCLUSION: The stool microbiota differed between asthmatic and nonasthmatic young people in Brazil. Asthma was associated with higher Bacteroides levels, which correlated with nasal IL-4 concentration.
Keywords: Asthma; gut microbiota; microbiome; stool